Geographic Information System for Mapping Poverty Levels In East Sumba District - Huluuma, Melania Mburu; Talakua, Alfrian Carmen; Uly, Hawu Yogia Pradana (MALCOM: Indonesian Journal of Machine Learning and Computer Science, 2024)
Poverty issues in East Sumba Regency, East Nusa Tenggara Province, which is faced with a high poverty rate. The obstacle of mapping areas with poor people that are difficult to identify is the main focus. Through qualitative and quantitative approaches, this research applied the Extreme Programming (XP) method to develop a web-based Geographic Information System (GIS), aimed at mapping poverty areas. XP was applied to ensure flexibility, adaptability, and active stakeholder participation in the application development. The main objectives were to produce an effective GIS application, provide accurate information for the government and stakeholders, and improve the effectiveness of poverty reduction programs. This research is expected to contribute to the design of programs that are more targeted, effective, and can improve community welfare in East Sumba Regency.